Turismo interno y estrategias de marketing para el desarrollo turístico en la Parroquia Rural de Mata de Cacao - Rosero Jara, Cristhofer Santiago (2021)
Internal tourism is one of the activities that get the most economic profits in our country, therefore it is particularly important to make an analysis in depth of the region named Mata de Cacao, parroquia Febres Cordero, province of Los Rios. This case study seeks to analyze the internal tourism of Mata de Cacao, Febres Cordero sector, to suggest effective marketing strategies. Also, as a second but not less important point, we are trying to find out if there has been promotional campaign looking for an influx of tourists in Febres Cordero. The following analysis is focused on exploring and figuring out how important is internal tourism and marketing, to promote and improve the life conditions of the people who live in the studied regions, also this study serves to verify if there is knowledge about the touristic potential that our natural attractive possesses.